(untitled) (Herald of the National Children’s Medical Center, 2022)
In order to study changes in hemostasis, 77 newborns with hypoxic-ischemic lesions of the central nervous system were examined. Depending on the neurological status and neurosonogram data, all children were divided into three groups: healthy children (group I); premature newborns with moderate CNS damage without hemorrhagic manifestations (group II); premature newborns with severe CNS damage, with hemorrhagic manifestations (group III). It is shown that the violation of hemostasis should be regarded as universal pathogenetic factors of the development of ischemic-hemorrhagic disorders that determine the development of cerebral deHciency of varying severity.